Plastics waste management : processing and disposal - Muralisrinivasan, Natamai Subramanian (Wiley, 2019)
"Within a specifc ecological-economic system, each material is generally connected to and also dependent on others. Moreover, plastics contribute to the overall integrity of this life system. However, since all plastics contribute to the functional scheme of things in waste generation, it is undoubtedly a very important issue. In particular, plastics provide key applications that are also unique; without plastics, the underlying ecological-economic system would be very different"-- Provided by publisher.
Keywords: Plastic scrap.; Factory and trade waste.; Plastics -- Environmental aspects.; elektronické knihy; electronic books